Measuring the quality of university library services, an applied study on library services at King Abdulaziz University in Jeddah | قياس جودة خدمات المكتبات الجامعية دراسة تطبيقية على خدمات مكتبات جامعة الملك عبدالعزيز بجدة - Abbas | عباس, Hicham Abdullah | هشام عبدالله (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The modern world is witnessing many changes in all fields, whether economic, political, social, or other... Globalization has also imposed the freedom of movement of material and human capital, as well as information and technology. Without any restrictions limiting this freedom, the world has become a small, sprawling village, which has called on many beneficiaries and those interested in the service sector to search for service institutions that are famous for the quality of service they provide. | يشهد العالم الحديث متغيرات عديدة في جميع الميادين، سواء كانت اقتصادية أم سياسية واجتماعية أو غيرها…، كما فرضت العولمة حرية انتقــال رأس الـمـــال المادي والبشــــري فضلا عن المعلومات والتقنية؛ دون أن تكون هناك أي قيود تحد من هذه الحرية حتى أصبح العالم قرية صغيرة مترامية الأطراف، مما دعا الكثير من المستفيدين وأصحاب الاهتمام بقطاع الخدمات إلى البحث عن مؤسسات خدمية تشتهر بجودة الخدمة التي تقدمها.